Organizational and Pedagogical Conditions of High School Pupils Tolerance Formation in the Process of Learning Social Science Subjects - Muliar, Oksana (Pedagogical Discourse, 2012)
Organizational and pedagogical conditions of activation of high school pupils tolerance formation in learning social science subjects are offered in the article.